HCI in practice: An empirical study with software process capability maturity model consultants in Brazil. Issue 11 (10th September 2018) - Guidini Gonçalves, Taisa; Marçal de Oliveira, Káthia; Kolski, Christophe
Abstract: Human‐computer interaction (HCI) and software engineering (SE) are undoubtedly important domains for the development of interactive systems. The quality of an interactive system is usually considered dependent on the user interface design and evaluation, which implies the use of HCI and SE approaches on the adequate software process. With the wide use of software process capability maturity (SPCM) models in the industry and their role of proposing best practices for software development and maintenance, some questions come up: To what extent are HCI approaches known and used to develop interactive systems? What is their level of use compared to SE approaches? To answer these questions, we conducted an empirical study in the Brazilian industry. Thirty‐six official consultants for the 2 SPCM models used in Brazil (CMMI‐DEV and MR‐MPS‐SW) provided us with their perception of knowledge and use concerning a set of predefined categories of approaches for HCI and SE that support the engineering practices of those SPCM models. By using a paired t test, we concluded that consultants of those models do not know and do not use HCI approaches as well as they know and use SE approaches. Moreover, they know little about HCI approaches, which may justify their poor use.